2021
DOI: 10.48084/etasr.4419
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Velocity Impact Loading on Self-Compacting Concrete Reinforced with Carbon Fiber Reinforced Polymers

Abstract: Self-Compacting Concrete (SCC) reduces environmental noise and has more workability. This research presents an investigation of the behavior of SCC under mechanical loading (impact loading). Two types of cement have been used to produce SCC mixtures, Ordinary Portland Cement (OPC) and Portland Limestone Cement (PLC), which reduces the emission of carbon dioxide during the manufacturing process. The mixes were reinforced with Carbon Fiber Reinforced Polymer (CFRP) which is usually used to improve the seismic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Heat treatment processes can be used to modify the surface and structural properties of low carbon steel in order to have a hard outer surface and a ductile and tough inner core, which is beneficial for engineering applications such as cams, gears, and shafts. These properties assist the resistance in wear and shock, thus extending the life of the component [1][2][3]. Carburizing is an ancient thermo-chemical heat treatment used to harden the surface of low carbon steel by diffusing carbon into it.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment processes can be used to modify the surface and structural properties of low carbon steel in order to have a hard outer surface and a ductile and tough inner core, which is beneficial for engineering applications such as cams, gears, and shafts. These properties assist the resistance in wear and shock, thus extending the life of the component [1][2][3]. Carburizing is an ancient thermo-chemical heat treatment used to harden the surface of low carbon steel by diffusing carbon into it.…”
Section: Introductionmentioning
confidence: 99%
“…The bending energy is subtracted from strain energy to determine the fracture work. The rotating kinetic energy can be determined by (10), which involves integration over the length of the specimen and the assumption of a linear velocity distribution along the beam's length. The hammer's momentum is quickly transferred to the beam when it strikes it.…”
Section: B Energiesmentioning
confidence: 99%
“…Previous researchers have indicated that when a structural element is subjected to an impact load, it elicits two distinct responses: a local response and a global response. The local response is primarily caused by the stress wave generated at the impact point, whereas the global response arises from the subsequent elastic-plastic deformation over an extended period throughout the structural member [5][6][7][8][9][10]. The failure of RC beams under impact loading raises significant concerns, with localized failures such as penetration, scabbing, perforation, and punching shear being the most commonly observed types of failure in RC elements subjected to impact loads.…”
Section: Introductionmentioning
confidence: 99%
“…When glass is utilized as an aggregate, its high alkali content facilitates the formation of the pozzolanic reactions and the inclusion of glass powder has a positive effect on the properties of concrete [14]. Additive fibers can improve concrete responsiveness under static and dynamic loads [15]. The cementitious compositions of RPC cause brittle failure in tension or compression, therefore fiber reinforcement is added [16,17].…”
Section: Introductionmentioning
confidence: 99%